The Effectiveness of Nitrogen Fertilization in Codiaeum variegatum L. and Sansevieria trifasciata L. and the Effects on Pb Accumulation: DOI: 10.32526/ennrj.18.3.2020.30 - Woro Lestari, Mahayu; Rosyidah, Anis; Purkait, Bulbul (Environment and Natural Resources Journal, 2020)
The use of (NH4)2SO4 fertilizer is vital in increasing plant growth and reducing the Pb content in soil. This study determined the ability of Codiaeum and Sansevieria to accumulate Pb due to (NH4)2SO4 fertilization and its effects on their growth rate. The ammonium fertilizer was applied three days after repotting according to these treatment levels: 0, 100, and 200 kg N/ha, denoted as P0, P1, and P2, respectively. The height of Codiaeum decreased by 45.04%, 24.67%, and 13.70% in treatment P0, P1 and P2, respectively, one week after repotting. The Pb concentrations in Codiaeum decreased with increasing doses of N fertilizer, while in Sansevieria, Pb concentrations increased with higher doses of N fertilizer. A reduction in the soil pH was seen with increasing dosage of N fertilization in Codiaeum, while the pH of the medium with Sansevieria was stable. Therefore, the effect of the different N doses, which causes a decrease in soil pH, was more significant in Codiaeum compared with Sansevieria. Furthermore, the highest value of TF was found in Codiaeum treated with 200 kg N/ha.